THE INFLUENCE OF LEADERSHIP STYLE, MOTIVATION, AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT BANK SUMUT USU BRANCH - Nugraha Ramadhan Sinaga (Transpublika Publisher, 2023)
Human resources play a crucial role in the functioning of any company. Therefore, it is imperative to prioritize the well-being and development of employees. This research aims to analyze the influence of leadership style, motivation, and work environment on employee performance at PT Bank Sumut USU Branch. This study adopts a quantitative approach, utilizing an associative method. The sampling technique employed is non-probability sampling with a purposive sampling technique, resulting in a sample size of 34 respondents. The data analysis includes instrument testing, validity testing, reliability testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The findings demonstrate that leadership style, motivation, and work environment significantly impact employee performance at PT Bank Sumut USU Branch, both individually and collectively. The coefficient of determination test reveals a strong relationship between leadership style, motivation, work environment, and employee performance, with an R value of 0.338. Furthermore, the Adjusted R Square value indicates that leadership style, motivation, and work environment can explain 78.7% of employee performance, while the remaining 21.3% is influenced by other variables not examined in this study.